The Influence of Ease, Security, and Benefits on the Decision to Use QRIS Payments in the Digital Era among Generation Z - Nada Khairiah; Dessy Handa Sari; Ramli Ramli (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
This study aims to analyze the influence of ease, security, and perceived benefits on the decision to use the Quick Response Code Indonesian Standard (QRIS) as a digital payment method among Generation Z in Penajam Paser Utara in 2025. The background of this research is the increasing adoption of digital technology in economic activities, including non-cash payment systems. QRIS is considered an efficient, secure, and practical solution to support the cashless lifestyle, especially among the younger generation. A quantitative approach was employed using a survey method involving 344 Generation Z respondents. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The results show that ease of use, security, and perceived benefits have a significant influence on the decision to use QRIS. Key driving factors include transaction simplicity, data security perceptions, and the perceived usefulness of QRIS in improving efficiency. These findings emphasize the importance of technological innovation in financial services and highlight the need for education and development of digital payment systems that are easy, safe, and beneficial, in order to improve financial inclusion in Indonesia. Keywords: QRIS; Ease; Security; Perceived Benefits; Generation Z; Digital Payment